2012
DOI: 10.1063/1.4772016
|View full text |Cite
|
Sign up to set email alerts
|

Increasing recoverable energy storage in electroceramic capacitors using “dead-layer” engineering

Abstract: The manner in which ultrathin films of alumina, deposited at the dielectric-electrode interface, affect the recoverable energy density associated with (BiFeO3)0.6–(SrTiO3)0.4 (BFST) thin film capacitors has been characterised. Approximately 6 nm of alumina on 400 nm of BFST increases the maximum recoverable energy of the system by around 30% from ∼13 Jcc−1 to ∼17 Jcc−1. Essentially, the alumina acts in the same way as a naturally present parasitic “dead-layer,” distorting the polarisation-field response such t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 18 publications
(19 reference statements)
1
39
0
Order By: Relevance
“…The stoichiometry (BiFeO 3 ) 0.4 –(SrTiO 3 ) 0.6 was targeted, however, EDX results [see in Ref. ] suggested that the resulting thin film was bismuth deficient and strontium rich than the nominal composition. Circular top electrodes of Platinum (500 μm diameter) were evaporated through a patterned mask.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The stoichiometry (BiFeO 3 ) 0.4 –(SrTiO 3 ) 0.6 was targeted, however, EDX results [see in Ref. ] suggested that the resulting thin film was bismuth deficient and strontium rich than the nominal composition. Circular top electrodes of Platinum (500 μm diameter) were evaporated through a patterned mask.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…[ 13 ] The utilization of a "dead layer" at the fi lm/electrode interface could wileyonlinelibrary.com be another way to further increase the energy density, especially for a large area device. [ 31 ] To benchmark the capability of the BNLBTZ thin fi lms for applications in energy storage devices, the energy densities of the BNLBTZ thin fi lms in the present work are compared with a number of promising materials previously reported ( Figure 6 and Supporting Information, Table S1). The energy densities in both the (100)-and (111)-oriented BNLBTZ thin fi lms reported here are signifi cantly better than previously reported leadbased (PZ, PLZT, PZN-PMN-PT, PLZST, etc.)…”
Section: Energy Storagementioning
confidence: 99%
“…Antiferroelectric (AFE) materials are promising candidates of great current interest for future high-energy and fast-speed storage capacitors, due to the field-forced phase transition into the ferroelectric state accompanied by large charge storage [1][2][3][4][5]. Thin films of AFE and ferroelectric (FE) materials are of particular interest due to their relevant applications in connection with microelectronic devices [4,6].…”
Section: Introductionmentioning
confidence: 99%